Una revisión sistemática de literatura sobre la violencia contra mujeres mayores en América Latina y el Caribe: ¿se ha alcanzado una perspectiva interseccional? - Ramos Bonilla, Gabriela (Pontificia Universidad Católica del Perú, 2021)
This article makes a critical and systematic review of 72 qualitative and quantitative studies related to the subject of violence against older women (VOW) in LAC between the years 2000 and 2020. It aims to evaluate to what extent they have managed to analyse this phenom- enon using an intersectional approach —as a gender— and age-based problem simultaneously and the gaps, limitations and main findings of this body of research. This review shows that this subject’s study has been dominated by the conceptual frameworks of «elder abuse» and «violence against women» (VAW). They approached this subject through a medical perspective and quantitative methodologies and failed to fully understand it since they addressed violence in a frag- mented way. In comparison, a novel group of studies carried out by social researchers through the conceptual framework of «intersectionality» approached violence from a life-course and phenomenological perspective. This research concludes that even though intersectional studies are still scarce in LAC, they show great potential to reveal the cumulative nature of violence, the interconnection between different lifetime experiences of abuse, to explore older women’s belief systems, their daily experiences of abuse, dilemmas, barriers and strategies for seeking help. This framework will allow the construction of theory inductively and grounded on contextualised evidence is a powerful weapon to confront former theoretical frameworks.

Este artículo hace una revisión crítica y sistemática de 72 investigaciones cualitativas y cuantitativas relacionadas con la violencia ejercida contra mujeres mayores de América Latina y el Caribe (ALC) entre los años 2000 y 2020 con el objetivo de evaluar en qué medida han logrado analizar este fenómeno desde un enfoque interseccional—vinculado con el género y la edad en simultáneo— y cuáles son sus brechas, limitaciones y principales hallazgos. Esta investigación demuestra que el estudio sobre este tema ha sido dominado por los marcos conceptuales del «maltrato a las personas adultas mayores» y la «violencia contra la mujer», así como también por una perspectiva médica y cuantitativa que no permiten comprender este problema cabalmente, pues abordan la violencia de manera fragmentada. En comparación, un grupo novedoso de estudios sociales utilizó un marco conceptual interseccional abordando la violencia desde un enfoque de curso vital y una perspectiva fenomenológica. A modo de conclusión se plantea que los estudios interseccionales, a pesar de ser aún escasos en ALC, poseen un gran potencial para la comprensión de la naturaleza acumulativa y la interconexión entre diferentes experiencias de abuso, así como explorar los sistemas de creencias de mujeres mayores, sus experiencias cotidianas de abuso, y sus dilemas, barreras y estrategias para buscar ayuda. Esta perspectiva permitirá la construcción de teoría adaptada a nuestros contextos culturales de forma inductiva y basada en evidencia contextualizada es un arma poderosa para enfrentar falencias de los marcos teóricos anteriores.
A critical literature review on violence against older women in Latin America and the Caribbean: has an intersectional research approach been achieved?
Keywords: Older women; Violence against women; Elder abuse; Intersectionality; Latin America and The Caribbean; Mujer adulta mayor; Violencia contra la mujer; Maltrato a las personas adultas mayores; Interseccionalidad; América Latina y el Caribe; https://purl.org/pe-repo/ocde/ford#5.04.03